Medical mimicry: abdominal tuberculosis presenting as surgical emergency - Hambolu, Eloho; Ishola, Sophia B.; Adeniyi, Adewale; Dedeke, Iyabode O. F.; Akande, Oluseyi; Arifalo, Gregory O. (International Journal of Contemporary Pediatrics, 2025)
Abdominal tuberculosis is a relatively uncommon but important differential diagnosis in patients presenting with abdominal symptoms, especially in regions with high TB prevalence. This case report describes an 11-years-old boy who presented with abdominal and scrotal swelling, along with intermittent fever, mimicking a surgical emergency. An initial clinical impression of ruptured appendicitis led to an exploratory laparotomy, which revealed copious serous fluid and widespread pale, firm seedlings throughout the peritoneal cavity. Histological examination of omental tissue showed chronic necrotizing granulomatous inflammation suggestive of tuberculosis. Despite inconclusive GeneXpert and microbiological findings, the clinical picture prompted a therapeutic trial of anti-TB medications. The patient responded remarkably, with complete resolution of symptoms and significant weight gain. This case underscores the diagnostic difficulty posed by abdominal TB and highlights the potential role of empirical anti-TB therapy in appropriate clinical contexts when diagnostic tools are limited or yield inconclusive results.